Integrating computational thinking into teacher education: A systematic literature review - Listiaji, Prasetyo; Molnár, Gyöngyvér (International journal of educational research, 2025)
•It is important to integrate computational thinking (CT) into teacher education.•Most research is concentrated on pre-service training and STEM subjects.•CT models used in teacher education are diverse.•Plugged activities and visual programming are most commonly employed.•Questionnaires and achievement tests are most frequent in assessing CT. Integrating computational thinking (CT) into teacher education is essential for preparing future teachers in the 21st century. This systematic literature review selected 43 journal articles (2014–2024) using the PRISMA standard to examine the subject area, CT model, intervention, tools, and assessments. The results show that the literature (1) focuses on STEM subjects, with most researchers using (2) the CT model, including decomposition, pattern recognition, abstraction and algorithm thinking, (3) plugged activity, (4) visual programming, and (5) questionnaires and achievement tests as assessment tools. Further potential research includes studies on non-STEM subjects, CT model testing, unplugged interventions, non-programming tools, and assessment validity and reliability. This study provides important and evidence-based insights for researchers in teacher education and development so that they can design more effective teaching strategies in integrating CT into in-service and pre-service teacher education.